Ribosome inactivation by Escherichia coli GTPase RsgA inhibits T4 phage - Fernández-García, Laura; Tomás, María; Wood, Thomas K. (Frontiers in Microbiology, 2023)
Bacteria must combat phages, and myriad bacterial anti-phage systems have been discovered that reduce host metabolism, for example, by depleting energetic compounds like ATP and NAD+. Hence, these systems indirectly inhibit protein production. Surprisingly, direct reduction of ribosome activity has not been demonstrated to thwart phage. Here, by producing each of the 4,287 Escherichia coli proteins and selecting for anti-phage activity that leads to enhanced growth, we identified that E. coli GTPase RsgA inhibits lytic phage T4 by inactivating ribosomes.